PENGARUH PELATIHAN LADDER DRILL 90 DEGREE ROTATION DAN LADDER DRILL ALI SHUFFLE TERHADAP PENINGKATAN DAYA LEDAK OTOT TUNGKAI DAN KECEPATAN - Shandy Pieter Pelamonia; Bayu Akbar Harmono (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2018)
Physical condition is a very important component in sports activities while they are achievement or learning. Explosive power leg muscle and speed of motion is the dominant component in sporting activities such as basketball, soccer, volleyball, martial art. The purpose of this study was to determinate This research is a "Quantitative" research method with quasi-experimental techniques, research conducted rigorously to determine the causes and effects between variables. Data analysis techniques in this study were to test the double normality test, homogeneity test, and hypothesis testing. The results of the analysis can be seen that the mean value of the ladder drill 90 degree rotation for increased explosive power has increased from the pretest (452.507) and posttest (482.220) while the speed of the pretest (4.4) and posttest (4.394). The ladder drill ali shuffle group found that the mean value of leg muscle explosive power had increased from pretest (461,269) and posttest (576,757), while the speed of the pretest (4,364) and posttest (4,360). For the control group, the mean value for leg muscle explosive power from pretest (450,738) and posttest (456,009).